2018
DOI: 10.1103/physreva.98.052502
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the difference in nuclear charge radius of Xe isotopes by EUV spectroscopy of highly charged Na-like ions

Abstract: The difference in mean-square nuclear charge radius of xenon isotopes was measured utilizing a new method based on extreme ultraviolet spectroscopy of highly charged Na-like ions. The isotope shift of the Na-like D1 (3s 2 S 1/2 -3p 2 P 1/2 ) transition between the 124 Xe and 136 Xe isotopes was experimentally determined using the electron beam ion trap facility at the National Institute of Standards and Technology. The mass shift and the field shift coefficients were calculated with enhanced precision by relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
(59 reference statements)
1
6
1
Order By: Relevance
“…Table. 9 displays comparison of the present and aforementioned studies [58,59,60]. We observed that our calculated FS values show an excellent agreement with [59], but the SMS results have a relative error of 5.7% and 2.4% in Ar 7+ and Xe 43+ , respectively.…”
Section: Isotope Shiftssupporting
confidence: 74%
See 2 more Smart Citations
“…Table. 9 displays comparison of the present and aforementioned studies [58,59,60]. We observed that our calculated FS values show an excellent agreement with [59], but the SMS results have a relative error of 5.7% and 2.4% in Ar 7+ and Xe 43+ , respectively.…”
Section: Isotope Shiftssupporting
confidence: 74%
“…We listed them in Table S9 (supplementary data). Previous results of IS factors are available from the MBPT calculations of Safronova and Johnson [58] for Ar 7+ , CIDF results of Tupitsyn et al [59] for Ar 7+ and Xe 43+ , and RMBPT and GRASP values of Silwal et al [60] for Xe 43+ . Table.…”
Section: Isotope Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterizing the nonlinearities arising from within the SM can provide new information about the nucleus [88], especially in combination with improved electronicstructure calculations. On the other hand, if evidence for a new boson should emerge from the improved measurements, it can be independently verified by performing similar measurements on other atomic species [10], such as Ca=Ca þ [13,89], Sr=Sr þ [12,14], Nd þ [90], or on highly charged ions [91][92][93][94], as well as on molecules like Sr 2 [95]. Unstable isotopes (e.g., 166 Yb with a half-life of ∼2.4 days) can be used to increase the number of points in the King Plot, providing strong further constraints on the origin of the nonlinearity.…”
mentioning
confidence: 99%
“…One such system was built at the National Institute of Standards and Technology (NIST) in 1993 and quickly began producing results 7 . Since its inception, the NIST EBIT has been used to take measurements across a variety of fields, including fundamental atomic physics [8][9][10] , spectroscopy of highlycharged ions for fusion and lithography [11][12][13] , laboratory astrophysics [14][15][16][17][18] , and nuclear physics 19 .…”
Section: Introductionmentioning
confidence: 99%